2016
DOI: 10.1039/c5dt04781a
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of steric hindrance modulates glutathione resistance and cytotoxicity of three structurally related RuII-p-cymene complexes

Abstract: The effect of steric hindrance on reactivity towards biomolecules while designing Ru(II)-η(6)-p-cymene based anticancer agents seems to be an important parameter in improving the activity and inducing resistance against glutathione (GSH) deactivation. Herein we present the structure, hydrolysis, anticancer activity and the effect of steric hindrance on deactivation by glutathione for three complexes, [Ru(II)(η(6)-p-cym)(L1)(Cl)](PF6) (1), [Ru(II)(η(6)-p-cym)(L2)(Cl)](PF6) (2) and [Ru(II)(η(6)-p-cym)(L3)(Cl)](P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…The structures of C1 – C4 and C6 (Ru– p ‐cymene complexes), and C8 and C14 (Ru–benzene complexes) were determined by single‐crystal XRD analysis. The complexes showed a pseudo‐octahedral geometry around the ruthenium ion with a piano stool form (Figure 4 and Tables S3 and S4 in the Supporting Information) [22–24] . On going from C1 (2.405 Å) to C3 (2.4206 Å), there was a noticeable increase in the Ru−S bond length, owing to the distancing of the phenyl group from the thiocarbonyl (C=S) moiety.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of C1 – C4 and C6 (Ru– p ‐cymene complexes), and C8 and C14 (Ru–benzene complexes) were determined by single‐crystal XRD analysis. The complexes showed a pseudo‐octahedral geometry around the ruthenium ion with a piano stool form (Figure 4 and Tables S3 and S4 in the Supporting Information) [22–24] . On going from C1 (2.405 Å) to C3 (2.4206 Å), there was a noticeable increase in the Ru−S bond length, owing to the distancing of the phenyl group from the thiocarbonyl (C=S) moiety.…”
Section: Resultsmentioning
confidence: 99%
“…The complexes showedap seudooctahedral geometry around the ruthenium ion with ap iano stool form (Figure 4a nd Tables S3 and S4 in the Supporting Information). [22][23][24] On going from C1 (2.405 )t oC3 (2.4206 ), there was an oticeable increase in the RuÀSb ond length, owing to the distancing of the phenyl group from the thiocarbonyl( C =S) moiety.T his increase was also observed in the case of C4 (2.4065 ), in which electron-donating ethyl groups are attached at the ortho positions of the terminal phenyl moiety, from which it can be concluded that the RuÀSb ond becomes weaker in such cases. In contrast, the RuÀSb ond was shorter in C6 (2.4025 ), ands till shorter in C14 (2.3875 ) compared with their parent complexes C1 and C8 (2.406 ), respectively,which signifies the strengthening of the bond in the presenceo fe lectron-withdrawing group(s).…”
Section: Molecular Structuresmentioning
confidence: 99%
“…The effect of steric hindrance on reactivity towards anticancer agents seems to be an important parameter in improving the activity. The cytotoxicity results strongly suggest that fruitful selection of groups with minimum steric hindrance and substituents nature with respect to donating and withdrawing effect may be a feasible pathway to derive anticancer agents . The molecules 4a and 4b contains electron donating influence from methyl and flouro groups, while O ‐ and P ‐ substituted groups were not shown major cytotoxicity.…”
Section: Resultsmentioning
confidence: 97%
“…In the next step, the aldol condensation reaction was designed to involve the nucleophilic attack of the enol form of MA2 to the protonated aldehyde moiety of the employed acetaldehyde derivatives affording MA3-MA5 products (Amarasekara and Ha, 2018). The aldehyde groups of these products were coupled with the primary amine groups of the utilized toluidine derivatives to generate Schiff-base containing products termed multifunctional coumarin derivatives (MC1-MC9) (Purkait et al, 2016;Al Zoubi et al, 2018;van Schijndel et al, 2019). The design of the synthetic plan, as well as the characterization data, confirmed that the chemical structures represented in Figure 1 could be attributed to the target synthetic products.…”
Section: Chemical Approachmentioning
confidence: 85%